2017
DOI: 10.1371/journal.pone.0175061
|View full text |Cite
|
Sign up to set email alerts
|

Effects of p53-knockout in vascular smooth muscle cells on atherosclerosis in mice

Abstract: In vitro and in vivo evidence has indicated that the tumor suppressor, p53, may play a significant role in the regulation of atherosclerotic plaque formation. In vivo studies using global knockout mice models, however, have generated inconclusive results that do not address the roles of p53 in various cell types involved in atherosclerosis. In this study, we have specifically ablated p53 in vascular smooth muscle cells (VSMC) in the ApoE-/- mouse model to investigate the roles of p53 in VSMC in atherosclerotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
0
7
0
1
Order By: Relevance
“…The role of p53 in regulating cell cycle progression and invasion is well known (Mak, 2011;Muller & Vousden, 2014). A number of studies have reported the anti-proliferative and anti-migrative roles of p53 in atherosclerosis (Cao et al, 2017;Guevara et al, 2001;Matsushita et al, 2000;Scheinman et al, 1999), and TP53 transcription is tightly regulated in the cell cycle progression (Boggs & Reisman, 2006;S. Wang & El-Deiry, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The role of p53 in regulating cell cycle progression and invasion is well known (Mak, 2011;Muller & Vousden, 2014). A number of studies have reported the anti-proliferative and anti-migrative roles of p53 in atherosclerosis (Cao et al, 2017;Guevara et al, 2001;Matsushita et al, 2000;Scheinman et al, 1999), and TP53 transcription is tightly regulated in the cell cycle progression (Boggs & Reisman, 2006;S. Wang & El-Deiry, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the result of vascular inflammation. P53 deficiency affected the vascular smooth muscle cell migration and proliferation, an indication of atherosclerotic lesion formation [ 116 ].…”
Section: Copdmentioning
confidence: 99%
“…TIMPs are endogenous protein regulators of the MMP family [30], promoting TIMP-2 expression contributes to retarded recruitment of monocytes to inflammatory sites including atherosclerotic plaques, interruption in intraplaque activity of MMP and facilitated stabilization of atherosclerotic plaque lesions [31]. Moreover, p53 has also been highlighted as a significant regulator of atherosclerotic plaque formation [32]. Knockdown of H19 has been revealed to inhibit glioma-induced angiogenesis and glioma-associated endothelial cell capabilities of proliferation, migration and tube formation by decreasing the expression of angiogenic factor vasohibin 2 through upregulation of miR-29a [33].…”
Section: Discussionmentioning
confidence: 99%